SELECTION OF VOCATIONAL EDUCATION OF STUDENTS WITH LEARNING DISABILITIES IN MALAYSIA: STUDENTS, PARENTS, AND TEACHERS` PERSPECTIVES - Ibrahim, Rohaizat; Razalli, Abdul Rahim; Handrianto, Ciptro; Rahman, M Arinal; Utami, Indah Wahyu Puji (IJIET (International Journal of Indonesian Education and Teaching), 2021)
This study aims to identify the tendency of students with learning disabilities in choosing the field of their vocational education. This study also highlights the perceptions of parents and teachers towards the vocational field chosen by the students. A survey method is used in this study which involves 351 students with learning disabilities, 336 parents, and 248 teachers in the State of Selangor, Malaysia. The findings of the study indicate that there are several constructs namely, realistic, investigative, artistic, social, entrepreneurial, and conventional which determine students with learning disabilities choosing the field of vocational education. Meanwhile, several factors that influence parents' perceptions of their child's choice of vocational education field have been discussed in this study. This study illuminates the phenomena and tendency of difficulties faced by students with learning disabilities in choosing their field of vocational education. In this regards, parents and teachers have an important role in providing support to students with special needs in their learning and vocational choices.